Family oral health and dental caries expenditures in children attended at a health center in Lámud, Peru, during the year 2023 - Tafur Chávez, Nestor Arturo (2024)
Objective: To determine the correlation between family oral health and dental caries costs in children attended at Centro de Salud de Lámud, Peru, during the year 2023. Materials and methods: Quantitative study, observational approach, cross-sectional design and analytical type. The sample consisted of 240 preschool children whose parents and/or guardians attended dental consultations at Centro de Salud Lámud. The selection was non-probabilistic and by convenience. Results: There was no statistically significant correlation between family oral health and dental caries expenditure in children attended at Centro de Salud Lámud during the year 2023 (p > 0.05). There was also no significant correlation between the oral health of the children attended and the dental expenses for dental caries in the same health center (p > 0.05). In addition, there was no statistically significant correlation between the oral health of the parent and the dental expenses for dental caries in the referred health center (p > 0.05). Conclusion: There is no correlation between family oral health and dental caries costs in children attended at Centro de Salud de Lámud during the year 2023.